INFLUENCE OF COUPLING OF INTERNAL AND EXTERNAL DEFECTS ON THE INITIATION OF AXLE CRACKS BASED ON CRYSTAL PLASTICITY THEORYCRACKS - ZHOU SuXia; SHANG Hao; ZHANG Zhao (Jixie qiangdu)
In order to study the effect of coupling between inner and outer defects of high⁃speed train axle on fatigue crack initiation， a multi⁃crystal finite element model of high⁃speed train axle was established on mesoscopic scale based on crystal plasticity theory The stress field and structural deformation around the inner and outer defects of axle were analyzed by tensile and impact tests， and the effect of inner and outer defects coupling on fatigue crack initiation was investigated Based on the characteristics of stress distribution and plastic strain energy density distribution， the crack initiation location was predicted. The results show that the interaction between two defects was stronger when the inner defect was closer to the outer defect， and the crack initiation was promoted when the inner inclusion defect was at the center of the model， the interaction between the two defects was minimal， and the external defects were the main factors leading to crack initiation.